2011
DOI: 10.1371/journal.pone.0026251
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Prolyl Oligopeptidases Using Molecular Docking and Dynamics: Insights into Conformational Changes and Ligand Binding

Abstract: Prolyl oligopeptidase (POP) is considered as an important pharmaceutical target for the treatment of numerous diseases. Despite enormous studies on various aspects of POPs structure and function still some of the questions are intriguing like conformational dynamics of the protein and interplay between ligand entry/egress. Here, we have used molecular modeling and docking based approaches to unravel questions like differences in ligand binding affinities in three POP species (porcine, human and A. thaliana). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 71 publications
(63 reference statements)
1
31
0
Order By: Relevance
“…An insertion of a disulfide bridge between the two domains packed them together in a close structure and impaired the catalytic activity [20], reinforcing the concept that a physical step involving conformational change is the ratelimiting step, rather than chemical catalysis [36]. In addition, MD simulation and amino acid substitution also showed a loop (residues 193-209 in porcine POP) that detaches from the protein structure and may play a direct role in gating/recruiting substrates, as the channel through the loop region is both more flexible and wider, and thus, the more likely access pathway to the active site [23,24]. Data from both experimental and computational studies have revealed that although POPs from different species show similar three-dimensional structures, differences among their primary sequences confer some divergent features such as conformational behavior, susceptibility to in- hibitors and substrate specificity [23].…”
Section: Prolyl Oligopeptidase (Ec 342126)mentioning
confidence: 77%
See 3 more Smart Citations
“…An insertion of a disulfide bridge between the two domains packed them together in a close structure and impaired the catalytic activity [20], reinforcing the concept that a physical step involving conformational change is the ratelimiting step, rather than chemical catalysis [36]. In addition, MD simulation and amino acid substitution also showed a loop (residues 193-209 in porcine POP) that detaches from the protein structure and may play a direct role in gating/recruiting substrates, as the channel through the loop region is both more flexible and wider, and thus, the more likely access pathway to the active site [23,24]. Data from both experimental and computational studies have revealed that although POPs from different species show similar three-dimensional structures, differences among their primary sequences confer some divergent features such as conformational behavior, susceptibility to in- hibitors and substrate specificity [23].…”
Section: Prolyl Oligopeptidase (Ec 342126)mentioning
confidence: 77%
“…Structural data obtained by crystallization, threedimensional modeling, molecular dynamics (MD), spectroscopic analysis and site-directed mutagenesis of POP family members of different species [15][16][17][18][19][20][21][22][23][24] have facilitated the understanding of how these structurally similar enzymes can present different biochemical features. In this section, we describe an overview of the structural properties of POP and OPB.…”
Section: Overall Structure and Catalytic Fea-turesmentioning
confidence: 99%
See 2 more Smart Citations
“…The active site is hidden in a large cavity formed by the interface of propeller and hydrolase domain [5]. The molecular dynamics simulation studies have suggested that opening of two domains is the only possible pathway for the substrate entry in POPs [6].…”
Section: Introductionmentioning
confidence: 99%